Missing voices: Profile and extent of acquired communication disorders in Aboriginal and non-Aboriginal adult stroke survivors in Western Australia using linked administrative records. Issue 1 (January 2016) - Katzenellenbogen, JM; Atkins, ER; Thompson, SC; Hersh, D; Coffin, J; Flicker, L; Hayward, C; Ciccone, N; Woods, D; McAllister, M; Armstrong, EM
Background: Limited data exist on the extent of specific functional sequelae, including acquired communication disorder, among Aboriginal stroke survivors, making planning of multidisciplinary services difficult. Aims: To obtain estimates of the extent and profile of acquired communication disorder in Aboriginal and non-Aboriginal adult stroke survivors in Western Australia and investigate potential disparities in receiving in-hospital speech pathology services among survivors with acquired communication disorder. Methods: Stroke cases surviving their first stroke episode during 2002–2011 were identified using Western Australia-wide person-based linked hospital and mortality data, and their five-year comorbidity profiles determined. The mid-year prevalence of stroke cases with acquired communication disorder was estimated for 2011. Regression methods were used to investigate determinants of receiving speech pathology services among acquired communication disorder cases. Results: Of 14, 757 stroke survivors aged 15–79 years admitted in 2002–2011, 33% had acquired communication disorder (22% aphasia/dysphasia) and 777 (5.3%) were Aboriginal. Aboriginal patients were more likely to be younger, live remotely, and have comorbidities. A diagnosis of aphasia was more common in Aboriginal than non-Aboriginal patients 15–44 years (p = 0.003). A minimum of 107 Aboriginal and 2324 non-Aboriginal stroke patients with acquired communication disorder lived in Western Australia in 2011. Aboriginal status was not associated with receiving in-hospital speech services among acquired communication disorder patients in unadjusted or adjusted models. Conclusions: The relative youth, geographical distribution, high comorbidity prevalence, and cultural needs of Aboriginal stroke patients with acquired communication disorder should inform appropriate service design for speech pathology and rehabilitation. Innovative models are required to address workforce issues, given low patient volumes.